ANALISIS NILAI TAMBAH KUE PIA PADA INDUSTRI RUMAH TANGGA KARYA â€œAN-NURâ€ DI KOTA PALU - Arifuddin Lamusa, Ahyadi (AGROTEKBIS, 2015)
This study aim was to determine the value added derived from green beans when processed into pia cakes at An-Nur Home Industry in Palu. The location was purposely chosen with the consideration that the home industry was the central production of pia cakes. Respondents in this study were the leader and three employees of the home industry which address is BTN Palupi Block I1 No. 12 South Palu Sub District of Palu. Primary and secondary data collected were analyzed using value added analysis according to Hayami method. The research results showed that the value added generated by the home industry was IDR 76,091.67 kg-1 with the value added ratio of 72%. This value indicates that for every IDR 100 of the pia product value increase will result in the value added of IDR 72.